2012
DOI: 10.1080/02640414.2011.624541
|View full text |Cite
|
Sign up to set email alerts
|

Intra-task variability of trunk coordination during a rate-controlled bipedal dance jump

Abstract: In this study, we investigated trunk coordination during rate-controlled bipedal vertical dance jumps. The aims of the study were to investigate the pattern of coordination and the magnitude of coordination variability within jump phases and relative to phase-defining events during the jump. Lumbar and thoracic kinematics were collected from seven dancers during a series of jumps at 95 beats per minute. The vector coding technique was used to quantify the pattern and variability of trunk coordination. Coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Coordination patterns have been analyzed in various sporting and human movement contexts including rowing, swimming, golf, karate, gymnastics, and athletics in disciplines such as triple jump and dancing . In each of these instances, coordination was explored by examining relationships between kinematic variables such as body joint or segmental kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination patterns have been analyzed in various sporting and human movement contexts including rowing, swimming, golf, karate, gymnastics, and athletics in disciplines such as triple jump and dancing . In each of these instances, coordination was explored by examining relationships between kinematic variables such as body joint or segmental kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to understand the dynamic patterns of adjustment during sauté that are used by ballet dancers to maintain the desired turnout. This is based on studies like Smith et al 33 that have elucidated how trunk coordination occurs at different stages of a bipedal jump, and support the premise that variability in coordination may be a key to success in the movement of skilled dancers. Reeve et al 34 observed through the technique of vector co-ding that experienced dancers do not increase the variability of movement execution on different floors, showing that they adapt easily.…”
Section: Discussionmentioning
confidence: 70%
“…4,10,32 Continuous methods of analyzing coordination, such as the vector coding method, quantify patterns of coordination between segments (intersegmental coordination) or joints (interjoint coordination) across the time series of a task. 26,27 Compared to single-joint and single-segment kinematics, these interjoint and intersegmental coordination analyses may have greater sensitivity to detect subtle kinematic differences between groups of subjects or between modes of gait with varying mechanical demands.…”
Section: T T Conclusionmentioning
confidence: 99%
“…The pattern of coordination for each interval of the time series can then be defined as inphase (both segments/joints moving in the same direction at the same time), antiphase (the 2 segments/joints moving in the opposite direction at the same time), proximal phase (motion occurring primarily in the proximal joint/ segment), or distal phase (motion occurring primarily in the distal joint/segment) using 45° bin widths (FIGURE 1A). 4,27 Inphase coordination is represented by coupling angles between 22.5° to 67.5° and 202.5° to 247.5°. Antiphase coordination is represented by coupling angles between 112.5° to 157.5° and 292.5° to 337.5°.…”
Section: Data Processingmentioning
confidence: 99%